Glucose Level and Body Mass Index (BMI) Among Chronic Psychotic Patients Treated with A Typical Antipsychotic (Olanzapine) or Traditional Antipsychotic or Both of Them. In Nasiriya City Iraq. - Hlail Wad’a Al Sayyad, Hussain (International Journal of Psychosocial Rehabilitation, 2020)
Background: Schizophrenic and manic depressive patients treated with olanzapine have a 1.5-2 times higher rate of diabetes mellitus and obesity in comparison with the normal population (1). It was observed that traditional antipsychotics are associated with hyperglycemia in uncontrolled studies (2). This study facilitates a chance to study the side effects of both typical and atypical antipsychotic drugs on glucose during prospective trials (3), with probable explanations related to increased body weight due to atypical antipsychotic blockage of hypothalamic H1 receptors or serotonergic 5-HT receptor antagonism. (4) Aims of Study: The Study assessed the glucose level and BMI through a period of treatment with olanzapine, a traditional antipsychotic, or both drugs on a study sample. Also, studying the effect of various risk factors like sociodemographic variables, type of treatment (T0T), duration of disease (DOD), and random blood sugar (RBS). Methods: Seventy patients (20 and 50 females) with chronic psychotic disorder or manic depressive psychoses were out outpatients studied in crosssectional approach. An established evaluation consist patients treated for many years with atypical, traditional antipsychotic, or both drugs, involving RBSglycated hemoglobin HbA1cand BMI for the period March 1 to September 1, 2019. DSM-IV criteria was used for diagnosis of mental disorders Ethics: Verbal and written consent was taken from patients and their relatives Result: Most of the patients were diagnosed with chronic psychotic or manic depressive psychoses or other psychiatric disorders treated for one year or more. 70 patients of study sample (20 male, 50 female) (48.6%) were on olanzapine (20%) Were treated with traditional antipsychotics (31.4%) were on both drugs; most of patients were obese (35.7%) weight (37.1%); 14.3study sample were diabetic; 85.7% were with normal HbA1C; other correlated variables to diabetes mellitus were studied in various statistical approaches Conclusion: Cross sectional study of sample treated with olanzapine, traditional antipsychotics or both to reveal level of HbA1cand other relevant variables